2009
DOI: 10.1051/limn/2009025
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of the invasive crayfish (Procambarus clarkiiGirard, 1852) at two marshes with differing hydroperiods

Abstract: -The population dynamics of the red swamp crayfish (Procambarus clarkii Girard, 1852) was studied from May 2005 to May 2006 in a pond (PCD) subjected to drought between June and December and in a continuously flooded rice field drainage channel (PMG) located in the Tejo river basin, Portugal. The proportion of females in the population was not independent from the season and was negatively correlated with both female and male maturation status. Male and female maturation was synchronous but males remained in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Growth model obtained by electronic length frequency analysis (ELEFAN), distinguished by sex, the histograms represent the distribution of the lengths of the crayfish samples; the curve represent the VBGF model for each size class. seasonal trend in the capture rates, as already observed in other studies (Anastácio et al, 2009;Chucholl, 2011;Dörr et al, 2012;Fidalgo et al, 2001;Gherardi et al, 2000;Scalici et al, 2010). In Preola Lake, the IDW-GIS analysis evidenced heterogeneous catch rates between areas near and far from the shore and between sexes and sampling sessions (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Growth model obtained by electronic length frequency analysis (ELEFAN), distinguished by sex, the histograms represent the distribution of the lengths of the crayfish samples; the curve represent the VBGF model for each size class. seasonal trend in the capture rates, as already observed in other studies (Anastácio et al, 2009;Chucholl, 2011;Dörr et al, 2012;Fidalgo et al, 2001;Gherardi et al, 2000;Scalici et al, 2010). In Preola Lake, the IDW-GIS analysis evidenced heterogeneous catch rates between areas near and far from the shore and between sexes and sampling sessions (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…The use of traps with entrances at the top is motivated by the fact that it will limit the capture of non-target species but the higher this type of trap is, the more difficult it is to catch crayfish. The large proportion of small individuals observed in SCG whatever the habitats (51.1 to 82.3%), at this stage of the life cycle of the species, likely reflected the real population structure of P. clarkii better (see also Correia, 1995;Anastácio et al, 2009). Indeed, P. clarkii exhibits properties of an r-selected species, including particularly high fertility (Gherardi, 2006), and, in the present study, large proportions of small individuals were found only when SCG were used.…”
Section: Discussionmentioning
confidence: 91%
“…Rodríguez et al, 2003;Ilhéu et al, 2007;Correia and Anastácio, 2008;Matsuzaki et al, 2009), there is a need to better understand and predict the ecological success of the species, and therefore its impact on ecosystems. For this, an investigation of the environmental factors influencing the population characteristics of P. clarkii is a good starting point and will be helpful in the development of ways to control the species (Alcorlo et al, 2008;Anastácio et al, 2009). Trapping is likely to be the most useful method for sampling active P. clarkii (Huner, 1988) since the species inhabits aquatic ecosystems which usually have turbid waters thus limiting the efficiency of techniques such as manual search, night viewing and electro-fishing.…”
Section: Introductionmentioning
confidence: 99%
“…It has been described that under certain circumstances this may also affect dispersion patterns (Gherardi and Barbaresi, 2000;Light, 2003). P. clarkii main recruitment period in Portugal is usually in September/October (Anastácio and Marques, 1995;Anastácio et al, 2009) and mating is during May-July. Although no differences in reproductive form were perceptible among 2010 and 2013 individuals, the 2013 tracking period was just after the usual mating period.…”
Section: Discussionmentioning
confidence: 99%